DETERMINANTS OF FIRM VALUE: THE MEDIATING ROLE OF PROFITABILITY AND THE MODERATING ROLE OF FINANCIAL DISTRESS - Mohamad Zulman Hakim; Dafa Ardiansyah Putra; Sri Asih Wulandari; Khansa Putri Kamila; Rayhan Agata Firmansyah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study investigates the impact of audit opinion, audit quality, ESG, and intellectual capital on firm value, with financial distress as a moderating factor. This study utilized a quantitative approach. The sample was selected using a purposive sampling method, consisting of 11 companies listed on the Indonesia Stock Exchange (IDX) and included in the ESG Leaders Index for the 2021–2024 period, yielding a total of 44 observations. The data were analyzed using panel data regression with the assistance of E-Views 12 software. The results show that ESG and carbon tax influence firm value, while audit opinion, audit quality, and intellectual capital do not. Financial distress moderates the effects of audit opinion, audit quality, ESG, and carbon tax on firm value. Financial distress does not alter the effects of intellectual capital on firm value. Profitability mediates the effect of ESG on firm value. Profitability does not mediate the effect of audit opinion, audit quality, and carbon tax on firm value.